การพัฒนารูปแบบการทดสอบเพื่อเพิ่มศักยภาพการเรียนรู้วิชาคณิตศาสตร์ในห้องเรียนที่มีการให้ข้อมูลย้อนกลับทันทีโดยใช้ระบบคอมพิวเตอร์ตามแบบการเรียนของผู้เรียน - ณภาภัช พรหมแก้วงาม (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The purpose of this study was to 1) develop the test-enhanced learning model of mathematics in classrooms with immediate feedback using computer systems based on students’learning style, 2) examine the quality of the test model, and 3) study the results of using the test model, and 4) evaluate the effectiveness of the test model. Research examples were 126 students form 5 classes of Mathayomsuksa 1, Chulalongkorn University Demonstration School. Each group of students consisted of learners with 6 different learning styles, i.e., independent, dependent, collaborative, avoidance, competitive, and participant. Research instruments were 1) a learning style questionnaire, 2) pre-test and post-test on solving one-variable linear equations and 3) computer-based test with immediate feedback on solving one-variable linear equations. Data were analyzed by using descriptive statistics and inferential statistics, i.e., mean, standard deviation, and Two-ways MANCOVA. Results were as follow:1. The test-Enhanced Learning Model of Mathematics in classrooms with Immediate Feedback Using Computer Systems Based on Students’ Learning Style has three components: learners, testing tools and test results. The test procedures are divided into three stages: pre-test, intermediate-test and post-test. After implementing the test-enhanced learning model of mathematics in classrooms with immediate feedback using computer systems based on students’ learning style, it was found that there was no interaction between learning style and feedback on the probability for answering the question correctly (F= 0.66, Sig.= 0.76 on students’ learning development (F= 1.48, Sig.= 0.16) as well as on students’ learning retention (F= 0.91, Sig.= 0.53)2. According to the quality assessment of the developed test-enhanced learning model, it was found that the content coverage was of the has the best fit, the communication and the appropriateness of the Test has an appropriate fit.3. The results of using the test-enhanced learning model of mathematics in classrooms with immediate feedback using computer systems based on students’learning style showed that different test model indifferently affect students’ learning ability. Most of the students have a growth score in a moderate level (59.61%). Overall, students and teachers agreed that the test-enhanced learning model of mathematics in classrooms with immediate feedback was at the most appropriate level.4. The developed test-enhanced learning model of mathematics in classrooms with immediate feedback using computer systems based on students’ learning style, was evaluated in a very high level in utility. The feasibility of the test has high level of effectiveness. The propriety of the Test has high level of effectiveness, and the accuracy has high level of effectiveness.